Metformin Attenuates Cognitive Deficits in Experimentally Induced Alzheimer’s Disease - Laxmianarayana Bairy Kurady (Journal of Global Pharma Technology, 2017)
A study was undertaken to evaluate the effect of metformin on learning memory inexperimentally induced Alzheimer’s disease in Wistar rats. A total of 30 Wistar rats were divided in tofive groups of six rats each. Group 1 served as control. In Group 2,3 and 4 Alzheimer’s disease wasinduced by administering aluminum chloride (17 mg/kg) orally to the animals for a period of 4 weeksonce daily. Group 1and 2 received distilled water, group 3 received rivastigmine (0.3mg/kg) and group 4and five received metformin 100mg/kg. All the rats were subjected to passive avoidance test. At the endof the experiment the rats were sacrificed and brain acetylcholinesterase level was estimated.Administration of aluminium chloride resulted in poor learning and memory and this was significantlyreversed by rivastigmine and metformin. In conclusion, the memory impairment induced by aluminumchloride was revered significantly by both rivastigmine and metformin.Keywords: Alzheimer’s disease, Metformin, Rivastigmine, Passive avoidance test, Acetylcholinesterase.